Protozoa-driven micro-food webs shaping carbon and nitrogen cycling in reservoir ecosystems - Xue Wang; Jinxian Liu; Baofeng Chai; Tiehang Wu (Environmental Microbiome)
Abstract Protozoa-driven micro-food webs are pivotal regulators of microbial community structure and carbon–nitrogen cycling. By mediating trophic cascades that regulate bacterial and algal populations, protozoa influence nutrient remineralization and energy flow. Their regulation is crucial for stabilizing biogeochemical processes and preventing harmful algal blooms. However, little is known about the detailed relationship between the traits of micro-food webs and carbon/nitrogen cycling processes. Using metagenomic data, we investigated the complexity and stability of micro-food webs in three distinct zones of the Fenhe Reservoir—the inflow river zone, shallow wetland, and deep-water zone—to assess their impacts on carbon and nitrogen cycling. Our findings revealed distinct spatial patterns in micro-food web complexity and stability, with the highest diversity and interaction density in inflowing river zones and a gradual simplification towards deep-water zones. Functional gene analysis shows significant differences in carbon degradation, fixation pathways, and nitrogen transformation processes, with shallow waters exhibiting strong microbial-mediated nitrification and denitrification, while deep waters rely on anaerobic nitrogen reduction pathways. Partial least squares path modeling (PLS-PM) indicated that protozoan-driven micro-food web structures regulate microbial functional differentiation, thereby influencing carbon and nitrogen cycle. Additionally, environmental parameters such as organic carbon concentration and nitrogen availability significantly shape microbial interactions and biogeochemical transformations. These findings highlight the intricate relationship between microbial community composition, food web stability, and elemental cycling, providing critical insights for reservoir ecosystem management and water quality optimization.